Building a Cybersecurity and AI Integrated Learning Pathway for Criminal Justice Professionals (Journal of The Colloquium for Information Systems Security Education, 2025)
With support from the National Science Foundation, The University of Washington Tacoma and North Dakota State University have developed scenario-based security curriculum and online showcase labs with interactive simulations and case studies across three progressive courses, revolutionizing cybersecurity education for Criminal Justice (CJ) professionals. By incorporating artificial intelligence into the curriculum, this project enhances CJ professionals’ capabilities. Our goal is to develop a skilled workforce of CJ professionals with cybersecurity and privacy knowledge, addressing the critical need for such cybersecurity expertise in CJ. Literature review, focus group survey results, course framework tailored for CJ professionals, example course modules, and implementation results are presented.
Keywords: Cybersecurity; Criminal Justice; Artificial Intelligence